2019
DOI: 10.1016/j.stemcr.2019.10.013
|View full text |Cite
|
Sign up to set email alerts
|

SOX21 Ensures Rostral Forebrain Identity by Suppression of WNT8B during Neural Regionalization of Human Embryonic Stem Cells

Abstract: SummaryThe generation of brain region-specific progenitors from human embryonic stem cells (hESCs) is critical for their application. However, transcriptional regulation of neural regionalization in humans is poorly understood. Here, we applied a rostrocaudal patterning system from hESCs to dissect global transcriptional networks controlling early neural regionalization. We found that SOX21 is required for rostral forebrain fate specification. SOX21 knockout led to activation of Wnt signaling, resulting in cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…SOX3 down-regulates Wnt signaling by interactions with β-catenin or by direct binding to the regulatory regions of Wnt target genes ( Zorn et al, 1999 ; Zhang et al, 2003 ). SOX21 restricts Wnt activity by interacting with β-catenin and subsequent interfering with the binding of TCF4/β-catenin complex to the WNT8B (Wingless-type MMTV integration site family, member 8B) enhancer ( Fang et al, 2019 ).…”
Section: Sox Interplay With Wnt/β-catenin Signalingmentioning
confidence: 99%
“…SOX3 down-regulates Wnt signaling by interactions with β-catenin or by direct binding to the regulatory regions of Wnt target genes ( Zorn et al, 1999 ; Zhang et al, 2003 ). SOX21 restricts Wnt activity by interacting with β-catenin and subsequent interfering with the binding of TCF4/β-catenin complex to the WNT8B (Wingless-type MMTV integration site family, member 8B) enhancer ( Fang et al, 2019 ).…”
Section: Sox Interplay With Wnt/β-catenin Signalingmentioning
confidence: 99%
“…RNA samples of undifferentiated hESCs (day 0) and NPCs from these three groups at days 4 and 8 were collected for RNA-seq ( Figure 3 C). Compared with our previously published RNA-seq data of WT samples ( Fang et al., 2019 ), DEGs were identified ( Figure 3 D). Among the three groups of NPCs, SOX1 -KO gave rise to the most DEGs in the CT1.0 group and the least DEGs in the IWP2 group ( Figure 3 D), suggesting that SOX1 -KO affected NPCs of the CT1.0 group most.…”
Section: Resultsmentioning
confidence: 73%
“…Moreover, both up- and downregulated DEGs enriched the term of WNT signaling. In addition, based on our previously published dataset ( Fang et al., 2019 ), clustering analysis of DEGs revealed that the SOX1 -KO NPCs (CT1.0) were grouped with WT NPCs of CT0.8 and CT0.4 groups ( Figure 3 F), suggesting that the regional identity of SOX1 - KO NPCs of the CT1.0 group was closer to that of WT NPCs of CT0.8 and CT0.4 groups than to that of WT NPCs of the CT1.0 group. In contrast, the SOX1 -KO NPCs treated with IWP2 or 0.4 μM CT were grouped with WT NPCs under the same treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have shown that SOX21 is required for reprogramming to the pluripotent state and regulates the anterior-posterior identity in the adult mouse intestine (Kuzmichev et al, 2012). Other laboratories have reported SOX21 roles in embryonic versus extraembryonic fate at the 4-cell stage (Goolam et al, 2016), later events in forebrain development (Fang et al, 2019), and adult hippocampal neurogenesis (Matsuda et al, 2012). These data suggest that SOX21 repeatedly interacts with other class B SOX genes (SOX1, 2, and 3) to regulate major morphogenetic decisions.…”
Section: Resultsmentioning
confidence: 99%